1990
DOI: 10.1159/000186043
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Angiotensin-Converting Enzyme Inhibitor on Renal Function and Glucose Homeostasis in Diabetics with Hypertension

Abstract: The antihypertensive efficacy of enalapril and its effects on renal function and glucose homeostasis were investigated in 9 hypertensive patients with non-insulin-dependent diabetes mellitus. Enalapril therapy produced a significant fall in blood pressure (BP) (p < 0.05) and a significant increase in renal blood flow (p < 0.05) without a change in glomerular filtration rate. Furthermore, fasting plasma glucose was significantly reduced (p < 0.01). Similarly, M value, as an index of plasma glucose control in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…(27) 15 (30) Body mass index (kg/m2)24 8 (3 0)25 2 (2 9) test was used to compare the rates of conversion from Supine blood pressure (mm Hg) 166/91 (16/9) 174/92 (17/13) normoalbuminuria to abnormal albuminuria between Erect blood pressure (mm Hg) 167/94 (16/12) 171/94 (19/14)Mean arterial blood pressure (mm Hg) 117 (9) 120(12) the treatment groups. Repeated measures analysis of Glycatedhaemoglobin (%/)9 8 (1-7) (1 7)variance was used to test for the effects of treatmentPlasma fructosamine (mmol/l) 2 3 (0Q23) 2 3 (0-23)Fasting plasma glucose(mmol/l) 80 (21) 83(25) and its duration.…”
mentioning
confidence: 99%
“…(27) 15 (30) Body mass index (kg/m2)24 8 (3 0)25 2 (2 9) test was used to compare the rates of conversion from Supine blood pressure (mm Hg) 166/91 (16/9) 174/92 (17/13) normoalbuminuria to abnormal albuminuria between Erect blood pressure (mm Hg) 167/94 (16/12) 171/94 (19/14)Mean arterial blood pressure (mm Hg) 117 (9) 120(12) the treatment groups. Repeated measures analysis of Glycatedhaemoglobin (%/)9 8 (1-7) (1 7)variance was used to test for the effects of treatmentPlasma fructosamine (mmol/l) 2 3 (0Q23) 2 3 (0-23)Fasting plasma glucose(mmol/l) 80 (21) 83(25) and its duration.…”
mentioning
confidence: 99%
“…More importantly, there may be a difference between the effects of hyperinsulinaemia and insulin resistance in the development of hypertension. It has been well documented that people with essential hypertension, but not secondary hypertension[50], are more likely to suffer from insulin resistance and hyperinsulinaemia[1–7,30–51]. Similarly, hypertension is prevalent in NIDDM and obese patients, conditions that also are associated with various degrees of insulin resistance.…”
Section: Insulin Resistance and Blood Pressurementioning
confidence: 99%
“…It appears that the effect of insulin on SNS activity is direct and not simply baroreceptor mediated[54]. Insulin does not appear to cause mass activation of SNS activity but increases selective nerve activity[18–54]. The brain areas that have been associated with insulin's activation of sympathetic activity[54] are also the sites of the central pressor actions of Ang II[55].…”
Section: Insulin and The Sympathetic Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, severe hypoglycaemic episodes have occurred only a few hours or days after starting treatment with an ACE inhibitor [ 13, 14]. However, a large number of clinical studies, usually uncontrolled, brief and covering few patients [ 15, 16], have found that ACE treatment had no significant effect on glycaemic control in NIDDM or on insulin and C‐peptide levels [ 17] and only a few have indicated an improvement, with reduction in fasting blood glucose [ 18] or glycosylated haemoglobin (HbA 1c ) [ 19, 20].…”
Section: Introductionmentioning
confidence: 99%